Synthesis of Difluoromethyl-Substituted Quinazolines through Selective Difluoromethylation - Peng, Jing; Hu, Ludan; Chen, Mu-Wang; Deng, Zhihong; Peng, Yiyuan (Synthesis, 2021)
A highly selective difluoromethylation of quinazolines has been achieved by using commercially available ethyl bromodifluoroacetate as difluorocarbene precursor, providing the corresponding difluoromethyl substituted quinazoline derivatives with up to 83% yield.
Keywords: difluoromethylation; quinazoline; ethyl bromodifluoroacetate; difluoromethyl substituted quinazoline; difluorocarbene